Lupine as a potential agent against diet-induced obesity through adenosine monophosphate-activated protein kinase pathway: crude oil versus nanoemulsion formulations - Omar Mahmoud Mohafez; Ibrahim Abdelrahman Alhaider; Tamer Mohamed Shehata; Maged Elsayed Mohamed (Universidade de São Paulo, 2020)
Obesity represents a major challenge to the pharmaceutical community due to the minimal availability of anti-obesity drugs and the drawbacks of current weight-loss agents. The study described herein presents lupine oil, in two pharmaceutical formulations, as a potential anti-obesity agent via its effect on different physiological, biochemical, and hormonal parameters. Rats were divided into two groups; one group was continued on a standard commercial rodent diet and served as the non-obese control. The other group was fed a high-fat diet for 7 weeks to prepare an obese rat model. Then, the obese rats were divided into groups to receive 100 mg/kg of the crude lupine oil or nanoemulsion for 10 or 20 days. Lupine oil showed a potent body weight-reducing effect and improved insulin resistance. The oil altered obesity-induced hyperlipidemia and it enhanced the leptin/adiponectin/AMPK hormonal system in epididymal fat, serum, and liver, to which all the above physiological activities could be attributed. The nanoemulsion formulation of lupine oil significantly amplified the activity for all the above physiological and hormonal parameters when compared to the crude oil formulation. Lupine oil nanoemulsion could be used as a potential drug against diet-induced obesity.